Sensory Stimulation of Oxytocin Release Is Associated With Stress Management and Maternal Care - Takahashi, Toku (Frontiers in Psychology, 2021)
It has been shown that various types of stress initiate different physiological and neuroendocrine disorders. Oxytocin (OT) is mainly produced in the supraoptic nucleus (SON) and paraventricular nucleus (PVN) of the hypothalamus. Hypothalamic OT has anti-stress effects and attenuates the hypothalamic–pituitary–adrenal (HPA) axis. One mechanism behind the anti-stress effects of OT is mediated through the inhibition from GABAA receptors on corticotropin releasing factor (CRF) expression at the PVN. Various manual therapies such as acupuncture, transcutaneous electrical nerve stimulation (TENS) and massage initiate the stimulation of somatosensory neurons of the body. It is well known that TENS simulates OT expression while it inhibits CRF expression at the PVN following chronic stress loading in rodents. Upregulation of OT expression at the hypothalamus is activated by the somatosensory stimulation, which is mediated via the spinothalamic pathway (the conection between the spinal cord and hypothalamus). Thus, somatosensory stimulation is beneficial in treating stress-associated symptoms. Hypothalamic OT is associated with the social behaviors, including maternal care and affiliation. Childhood neglect and/or child abuse are severely responsible for deleterious long-term effects on the cognitive/social activity, and behavioral development. At parturition, a profound amount of OT is released into the systemic circulation in response to vaginal and cervical stimulation caused by the body of fetus, which induces the onset of maternal behavior. Peridural anesthesia effectively impairs the sensitivity to vaginal and cervical stimulation at parturition. OT levels in cerebrospinal fluid is significantly reduced following peridural anesthesia. The vaginal delivery mothers had significantly more OT pulses than the Caesarian section (CS) mothers. Due to low levels of endogenous OT, maternal behavior could be interrupted by epidural anesthesia and CS at parturition, because of the reduction of the usual sensory input from the genitalia.